New Forms of Antisemitism, the Law, and the Politics of Gender and Sexuality in Contemporary France - Chetcuti-Osorovitz, Natacha; Teicher, Fabrice (2018)
Since 2012, hundreds of thousands of people mobilized and demonstrated against a French law that made both marriage and adoption possible for same-sex couples. In these demonstrations, seemingly heterogeneous groups and political traditions came together against those they saw as common enemies, namely Jews, LGBT people and feminists. Are these paradoxical alliances new? How have they transformed the public space and the imaginary of citizenship? The analysis of these activist repertoires shows that the ethos of anti-modernism, which has historically characterized reactionary groups, expressed itself through an obsessive focus and fear of the alleged undoing of gender, which is seen as emblematic of a post-modern society. Whether online or in demonstrations, a collection of political actors, ranging from the far-right to post-colonial second-generation groups, join forces in denouncing mass media, capitalism, and human rights, which they believe to be avatars of the decadence of their postmodern world. Their activism has reshaped the French political landscape.
Online-Ressource
Open Access; Online erschienen am 30.05.2018
DOI: https://doi.org/10.1515/actap-2018-0001